Unpacking Micro-Learning Effectiveness: An Integrative Systematic Review of Design-Oriented Dimensions - Maulana Paramaditya Ananta; Muhammad Syifa'ul Qolby; Heri Miarto (Galaxy: Jurnal Pendidikan MIPA dan Teknologi, 2026)
Micro-learning is an instructional approach that delivers content in small, focused units to promote efficient and flexible learning. Although numerous studies have reported positive effects of micro-learning, existing evidence remains fragmented and often focuses on isolated variables without an integrative design-oriented perspective. This study aims to examine the effectiveness of micro-learning by synthesizing key aspects and design considerations that support its successful implementation. A Systematic Literature Review (SLR) was conducted following the PRISMA 2020 framework. Eight peer-reviewed articles from reputable academic journals were selected through strict inclusion and exclusion criteria to ensure methodological rigor, relevance, and alignment with the research objectives. While the limited number of reviewed studies may constrain the generalizability of the findings, this focused selection enables an in-depth and critical synthesis of evidence related to micro-learning design and effectiveness. The findings indicate that the effectiveness of micro-learning is influenced by three interrelated aspects: learners, content, and technology. Learner-related factors include engagement, satisfaction, performance, efficiency, and social interaction. Content-related factors emphasize cognitive load reduction, knowledge retention, and practical application, while technological factors highlight accessibility, contextualization, feedback, and interactivity. Overall, the study suggests that micro-learning can serve as an effective instructional approach when designed by integrating learner needs, content structure, and appropriate technological support to enhance learning outcomes and learner experiences across diverse educational contexts.